EFFECTS OF CRUDE SUGARCANE FACTORY EFFLUENT ON THE MORPHOLOGICAL AND BIOCHEMICAL PARAMETERS OF CHICKPEAS - Mohd. Suhail; K.P. Singh; Imran Ali (Indonesian Agency for Agricultural Research and Development, 2020)
Waste released from sugar factories has a huge amount of inorganic and organic matter whose effect on plant is different when used in different concentrations. Hence, the effects of sugar factory effluent on the morphological and biochemical parameters of chickpeas (Cicer arietinum Linn.) were studied by using the different concentrations of effluent for irrigation of chickpeas plant. The experiment was conducted at Botanical Garden, Department of Biochemistry, Bhaila (PG) College, Bhaila (Saharanpur), Uttar Pradesh. In the experiment, pots were arranged in a completely randomized design, replicated by six times and were labeled for the various treatments viz. 0%, 10%, 25%, 50%, 75% and 100% v/v. After that, chickpea plants were grown up to 10 days, in the soil irrigated with different concentrations of sugar factory effluent. It was observed that sugar factory effluent promoted the growth of chickpea seeds at 10–25% concentration, but its lethal impacts were noted when concentrations were above 50–100%. Hence, it was found that at lower concentrations (upto 25%), sugar factory effluent behaves as compost for better growth of chickpeas, but at high concentrations, it shows toxicity and behaves as a pollutant. Moreover, it makes the speed of biochemical reactions slow in chickpeas. Therefore, sugar factory effluent can be used for irrigation of chickpeas after proper dilution.